Transparency, Accountability, and Customer Trust in Islamic Banking: A Panel Data Analysis from Selected OIC Countries - Zulfikar Hasan; Muhamad Abduh; Romzie Rosman (Jurnal Magister Ekonomi Syariah, 2025)
This study examines how transparency and accountability shape customer trust in Islamic banking across selected OIC countries. Using panel data from 2010–2023, the analysis captures cross-country and time variations to reflect differences in institutional settings and developments over time. Governance and performance metrics are employed to represent transparency and accountability, while customer trust is proxied by deposit-related indicators. Applying fixed effects and system GMM estimations, the findings reveal a coherent pattern: transparency plays a dominant role in strengthening customer trust, as clear disclosure and accessible information directly reduce information asymmetry and enhance perceived Shariah credibility. Accountability also contributes positively, but its impact is comparatively weaker, reflecting the more indirect and internally oriented nature of accountability mechanisms. Importantly, transparency and accountability reinforce each other, indicating that trust is most effectively built when open communication is supported by robust governance structures. These results extend the Islamic finance literature by highlighting governance as a key driver of non-financial outcomes. Policy implications suggest the need for harmonized governance frameworks across OIC countries, with particular emphasis on strengthening transparency as a foundation for sustainable trust in Islamic banking.